The Effect of Social Support and Self-Efficacy on Learning Outcomes - Syidad, Ahmad Wildan; Ilmiyah , Bachrotul; Sofi, Natilatus; Amin , Saiful (SOSEARCH : Social Science Educational Research, 2024)
The purpose of this study was to examine the effect of social support and self-efficacy on student learning outcomes. The research method used was mixed methods with a sequential explanatory design. Multiple regression analysis was used to collect quantitative data on how the two variables affect learning outcomes, and in-depth interviews were used to collect qualitative data to provide a more thorough assessment. Students of the Department of Social Science Education (PIPS) at Maulana Malik Ibrahim State Islamic University Malang were the subjects in this study. The results showed that social support and self-efficacy did not have a statistically significant influence on student learning outcomes. However, qualitative data shows that social support is very influential to increase students' emotional support and help them in facing academic challenges. Students who have high self-efficacy also usually use more structured study techniques and have more confidence in their ability to complete academic tasks.